Impact of Dentinal Tubule Orientation on Dentin Bond Strength - Guo, Jing; Wang, Li-ping; Zhu, Jia; Yang, Jian; Zhu, Hong-shui (Current medical science, 2018)
Summary This study aimed to determine the impact of dentinal tubule orientation on dentin bond strength to provide a reference for clinical cavity preparation in resin-bonded restoration. Patients aged 13–16 years were selected, including 18 males and 21 females. Forty-eight human maxillary first premolars from orthodontic extractions were chosen to prepare the test models with the dentinal tubule orientations perpendicular and parallel to the bonding substrate. The test models in the vertical and parallel groups were divided into three groups: total-etching with 20% phosphoric acid, total-etching with 35% phosphoric acid and self-etching, with the dentinal tubule surfaces bonded with composite resin blocks in each group. After the standard test models of dentinal tubule-composite resin blocks were placed in distilled water and stored at 37°C for 24 h, shearing tests were performed using a universal material testing machine at a crosshead speed of 0.5 mm/min. The bond strength values in the vertical group were 19.33±1.59 MPa for the 20% phosphoric acid group, 21.39±2.34 MPa for the 35% phosphoric acid group, and 16.88±1.54 MPa for the self-etching group. The bond strength values in the parallel group were 24.53±1.99 MPa for the 20% phosphoric acid group, 25.16±2.88 MPa for the 35% phosphoric acid group, and 20.83±1.99 for the self-etching group. After using same total-etching adhesive, the shear bond strength of the parallel group was higher than that of the vertical group, and the difference was statistically significant ( P <0.05). Regardless of vertical group or parallel group, the difference in the bond strength value between the total-etching groups and the self-etching group was statistically significant ( P <0.05). It was concluded that the dentin bonding substrate which was parallel to the direction of the dentin tubule achieved an improved bond strength; the total-etching adhesives achieved higher bond strengths in dentin bond than the self-etching adhesives.